Biological Mechanisms of Enterotoxigenic Bacteroides fragilis Toxin: Linking Inflammation, Colorectal Cancer, and Clinical Implications - Seyedesomaye Jasemi; Paola Molicotti; Milena Fais; Ilaria Cossu; Elena Rita Simula; Leonardo A. Sechi (Toxins, 2025)
Enterotoxigenic Bacteroides fragilis (ETBF) has emerged as a gut microbiome pathogen that can promote intestinal inflammation and contribute to colorectal cancer (CRC). Its principal virulence factor, the Bacteroides fragilis toxin (BFT), is a zinc-dependent metalloprotease that disrupts epithelial barrier integrity, initiates inflammatory signaling pathways, and enhances epithelial proliferation. Although growing evidence supports a link between ETBF and CRC, some inconsistencies across studies highlight the need for further investigation into the molecular mechanisms underpinning BFT-mediated pathogenesis. This review examines the biological structure and activity of BFT, with a focus on its role in epithelial injury, inflammatory responses, and tumorigenesis. In addition, we discuss current challenges in the detection and characterization of ETBF and BFT, including technical limitations in clinical diagnostics and methodological variability across studies. Recent advances in multi-omics technologies, molecular diagnostics, nanobody-based detection platforms, and probiotic intervention are also highlighted as promising avenues for improving ETBF identification and therapeutic targeting. Future research integrating systematic molecular profiling with clinical data is essential to enhance diagnostic accuracy, elucidate pathophysiological mechanisms, and develop effective interventions against ETBF-associated diseases.